Herding behaviour in African stock markets: evidence from South Africa, Nigeria, Egypt & Kenya - Swart, Hermanus (School of Economics, 2025)
In the presence of herding, collective investor behaviour tends to gravitate toward the same or similar investments. When herding behaviour becomes widespread, it can create asset bubbles or market crashes through panic-driven buying and selling. Consequently, comprehending how markets might react during periods of crisis becomes crucial for effectively hedging against artificially inflated asset prices. The objective of this paper is to examine the herding behaviour of investors in African markets – namely South Africa, Nigeria, Egypt and Kenya – using weekly and monthly stock data from January 2000 to October 2023. The study applies the cross-sectional standard deviation of returns (CSSD) and the cross-sectional absolute deviation of returns (CSAD) to examine herding in both normal and turbulent times, particularly during periods of significant turbulence such as the Global Financial Crisis (GFC) in 2008/9 and the recent COVID-19 pandemic. The findings indicate the existence of herding behaviour in the four African stock markets across various periods, with herding being less prominent during highly turbulent phases like the GFC and the COVID-19 pandemic. Additionally, the study reveals a significant spillover from the South African stock market to Nigeria and Kenya during the GFC and to Egypt during the COVID-19 pandemic. Furthermore, U.S. investor sentiment, represented by the VIX index, does not appear to influence herding behaviour in African stock markets. This would suggest that the African markets are correlated and that there are instances of high indications of herding behaviour.